Forming tools for integrated assets management of commercial organizations - M. V. Galazova (Вестник Северо-Кавказского федерального университета, 2024)
Introduction. To achieve effective assets management of commercial organizations, it is important to use an integrated approach.Goal. The purpose of the study is to methodically substantiate the complex tools of assets management of commercial organizations.Materials and methods. In the course of the research, the works of Russian and foreign authors have been studied, showing the essence of portfolio, cost approaches, methods, methods, tools for managing them, as well as the directions of strategy formation, asset management policy in commercial organizations. A.I. Basov, I. R. Vinokur, V.A. Galanov, A.A. Mugatarova, A.V. Tsvetkova and foreign authors: I. Ansoff, G. Assel, F. Bouquerel, A. Dayan, P. J. Landrevi, R. Lancar, J. Levy, Mercator D. Lyndon distinguish a portfolio approach to assets management of organizations. F. R. Eshugova, S.Y. Hut, E.I. Khalilova, V.V. Shapovalov denote a cost-based approach to the management of current assets of organizations. V. K. Bansal, J. F. Marshall, J. Sinki fragmentally consider complex asset management of commercial organizations.Results and discussion. Based on the analysis of debatable issues, the key idea of integrated asset management is presented, reflecting a single holistic view of assets, liabilities, off-balance sheet resources; the main methods of integrated assets management of commercial organizations are defined, including risk management, management of non-current, current assets, profitability, liquidity, scientific management, evaluation; assets management of commercial organizations is reflected in terms of implementation of their development strategies, assets management policies; the inclusion of portfolio and cost approaches in the tools of integrated assets management is argued; the key principles underlying integrated assets management are identified.Conclusion. As a result, a comprehensive toolkit for assets management of commercial organizations is substantiated, integrating portfolio, cost approaches, basic assets management methods, which are based on key principles. Its implementation is aimed at ensuring effective assets management of commercial organizations.